Developing a strategy for missions : a biblical, historical, and cultural introduction - Terry, John Mark, 1949-; Payne, Jervis David, 1974- (Grand Rapids, Michigan : Baker Academic, a division of Baker Publishing Group, 2013)
"In this addition to the highly acclaimed Encountering Mission series, two leading missionary scholars offer an up-to-date discussion of missionary strategy that is designed for a global audience. The authors focus on the biblical, missiological, historical, cultural, and practical issues that inform and guide the development of an effective missions strategy. The book includes all the features that have made other series volumes useful classroom tools, such as figures, sidebars, and case studies. Students of global or domestic mission work and mission practitioners will value this new resource" -- Publisher description.
Strategy defined -- The crafting of mission strategy -- Contemporary objections to missionary strategy -- Strategic planning in biblical perspective -- Missiological principles for strategy development -- The apostle Paul's missionary strategy -- Missions strategy in the early church -- Roman Catholic strategy -- Pioneer Protestant strategies -- Faith missions strategy -- Mission strategies on the American frontier -- The indigenous mission strategy -- The church growth movement -- Frontier strategies -- Contextualization strategies -- Understanding cultural research -- Developing a people-group profile -- Developing a communication strategy -- Discerning receptivity -- Discerning need -- Visioning for the future -- Forming a team -- Assessing the resources -- Setting goals -- Choosing appropriate methods -- Execution -- Evaluation.
Includes bibliographical references (pages 269-275) and indexes.
Keywords: Missions -- Theory